INFORMATION AVOIDANCE BEHAVIOR REGARDING HOAXES INDICATORS - Godwin, Raymond; Chairunnisa, Fanny; Fitri, Rani Agias (Faculty of Psychology, Diponegoro University, 2020)
Hoaxes have become a common phenomenon in Indonesia. The Indonesian Telematics Society Survey shows that even though Indonesian people understand the way in recognizing hoaxes, they Indonesia are not sure of being able to immediately recognize hoaxes. Based on previous studies, there are two reasons that lead to lack of the assuredness, namely, the idleness in using thinking skills and ignorance of hoax indicators in the news they read. This study aims to find the correlation between avoidance behavior toward information that can indicate hoax, critical skill, and individual perception of easiness in obtaining the information regarding hoaxes. Information Avoidance Scale and the Critical Skill dimensions of the Digital Literacy Scale were adapted to Bahasa Indonesia to measure the tendency of information avoidance and critical skills. Whereas an instrument to measure the perception of the easiness to obtain information was constructed independently. The results indicate that critical skills and perceptions of the easiness to obtain information have a negative correlation with the tendency to avoid information. However, because the correlation is poor, critical skills and perceptions of the easiness to obtain information do not adequately explain a person's tendency to avoid information that can help him to recognize hoaxes.Â